Studi Zooplankton di Danau Teluk Kota Jambi - Mahya Ihsan; Ummi Mardhiah Batubara; Hesti Riany; Ika Oksi Susilawati; Teguh Sumarsono (BIO-SITE |Biologi dan Sains Terapan, 2016)
Lake Teluk natural potential is very rich in zooplankton. However, the there are many untapped potential, so that appropriate unknown environmental factors to support the growth, reproduction, and abundance of zooplankton that is potential as fish food can be cultivated properly. Therefore, there needs to be research related to environmental factors and abundance of zooplankton in Lake Teluk Jambi city in order to see the natural potential of fish forage in the area. This study was conducted at three stations in the Lake Teluk Jambi and Biotechnology Laboratory, Faculty of Science and Technology, the Jambi University. The method used in this research was the survery and analysis. Measured parameters were factors abundance of zooplankton and the physical and chemical environmental factors. The identification results obtained three phyla of zooplankton (protozoa, rotifers and sponges) and 14 genuses that were Platytrichotus, Centropyxis,Perispira, Corythion, Acropisthium, Turania, Trinema, Euglypha, Enteroplea, Proalinopsis, Pedipartia, Trocospheera, Filinia, Meyenia. Analysis of physical and chemical environmental factors showed solubility values (DO) range 4,8 - 6,8 mg/L, the water temperature ranges from 29-30 °C and oxygen consumption (BOD) in the range of 3,7 to 6,6 mg/L relatively optimal for the growth of zooplankton, but have not found any zooplankton that have the potential to be cultivated as a natural fish feed.